Animation, plasticity, and music in Italy, 1770-1830 - Lockhart, Ellen (University of California Press, 2017)
"This pathbreaking study of Italian stage works reconsiders a crucial period of music history: the late eighteenth century through the early nineteenth century. In her interdisciplinary examination of the statue animated by music, Ellen Lockhart deftly shows how Enlightenment ideas influenced Italian theater and music and vice versa. As Lockhart concludes, the animated statue became a fundamental figure within aesthetic theory and musical practice during the years spanning 1770-1830. Animation, plasticity, and music in Italy, 1770-1830 begins with an exploration of a repertoire of Italian ballets, melodramas, and operas from around 1800, then traces and connects a set of core ideas between science, philosophy, theories of language, itinerant performance traditions, the epistemology of sensing, and music criticism."--Provided by publisher